(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
ABSTRACT The use of marine environments represents a central issue in contemporary environmental discussions, especially considering its relevance to biodiversity, the global economy and sustainable development. This paper presents the concept of the “Blue Amazon” doctrine, the evolution of territorial discussions of maritime space until the awareness of the relevance of seas and oceans for society and the necessary respect for the environment, as a diffuse right, which must be ecologically balanced. The general objective of the paper is to analyze the polluter-pays and protector-receiver principles from the perspective of the aforementioned doctrine. The specific objectives consist of a) examining the evolution of discussions on the Law of the Sea; b) describing and examining the “Blue Amazon” doctrine, presented by Wagner Menezes in conjunction with goal 14 of the sustainable development goals; c) analyzing legislation and conventions that regulate business activities according to the polluter-pays and protector-receiver principles, distinguishing these principles, as well as their compatibility with the “Blue Amazon” doctrine. The descriptive, deductive methodology is adopted, with a bibliographic review of legal works. It is concluded that the mere payment by the polluter for environmental damages can create a perverse incentive for financial analysis, in which compensation is assessed as compensatory, in view of profits obtained even if the violation is irreversible. Thus, ocean education plays a vital role in the protection and prevention of damage to marine environments. Keywords: Environmental law. polluter-pays principle. protector-receiver principle. sustainable use of the balanced environment. Blue Amazon doctrine.